Analisis Perkembangan Produksi Kelapa Sawit Berdasarkan Luas Lahan dan Jumlah Pabrik Kelapa Sawit (Studi pada Kabupaten Rokan Hulu): Penelitian - Daulay, Nisa Purnama; putri, Azzahwa alyani; Ramadani, Oktavia Nada; Agata, Elysia Vania; Hamid, Muhammad (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the development of palm oil production based on land area and the number of palm oil mills (PKS) in Rokan Hulu Regency from 2020 to 2024. This study uses a quantitative descriptive method with secondary data from the Central Statistics Agency and the Plantation Service. The analysis covers growth rates, land productivity, processing efficiency, and Pearson's correlation to determine the relationship between these variables. The results show that land area increased by 24.61%, production by 17.59%, and the number of mills by 105.56%. A very strong positive correlation was found between production and land area (r = 0.983) and the number of factories (r = 0.979). However, the decline in land productivity and processing efficiency indicates that production growth was mainly driven by land expansion rather than increased yields per hectare.